Patients' experiences of consultations with physician associates in primary care in England: A qualitative study. - Halter, M; Drennan, V; Joly, L; Gabe, J; Gage, H; De Lusignan, S (Wiley, 2017)
Physician associates are new to English general practice and set to expand in numbers.To investigate the patients' perspective on consulting with physician associates in general practice.A qualitative study, using semi-structured interviews, with thematic analysis.Thirty volunteer patients of 430 who had consulted physician associates for a same-day appointment and had returned a satisfaction survey, in six general practices employing physician associates in England.Some participants only consulted once with a physician associate and others more frequently. The conditions consulted for ranged from minor illnesses to those requiring immediate hospital admission. Understanding the role of the physician associate varied from 'certain and correct' to 'uncertain', to 'certain and incorrect', where the patient believed the physician associate to be a doctor. Most, but not all, reported positive experiences and outcomes of their consultation, with some choosing to consult the physician. Those with negative experiences described problems when the limits of the role were reached, requiring additional GP consultations or prescription delay. Trust and confidence in the physician associate was derived from trust in the NHS, the general practice and the individual physician associate. Willingness to consult a physician associate was contingent on the patient's assessment of the severity or complexity of the problem and the desire for provider continuity.Patients saw physician associates as an appropriate general practitioner substitute. Patients' experience could inform delivery redesign.